A new approach to combine multiplex networks and time series attributes: Building intrusion detection systems (IDS) in cybersecurity. (September 2021) - Iglesias Pérez, Sergio; Moral-Rubio, Santiago; Criado, Regino
Highlights: A new computationally and temporally efficient methodology to represent the relationships between assets through a multiplexed network whose edges include temporal attributes. A combination of two mathematical domains (signal processing and complex networks) increases the accuracy of each of them separately. An application of a new methodology in the cybersecurity domain provides promising results with a more computationally efficient effort. Abstract: Intrusion Detection Systems (IDS) are fundamental tools in cybersecurity environments. In this paper, we present a new methodology for the creation of intrusion detection systems (IDS) based on a strategy that combines the use of multiplex networks and time series analysis to provide a probability that an IP address be an attacker in a certain time. This approach reduces the number of alerts to a small number of IP addresses as well as the computation effort by not having to analyze each event independently. The evaluation of all traffic happens only at pre-defined times. The methodology relies on both the original utilization of some unsupervised machine learning techniques and on the use of certain time series attributes and their representation as a complex multiplex network, achieving a very significant reduction in the dimensionality of the resulting data representation. The result is a very effective intrusion detection system in large corporate environments and a new approach in the representation of the analyzed data as shown in the real case presented.